Inequality and opportunity : the relationship between income inequality and intergenerational transmission of income - Pérez Arce, Francisco (Research report (Rand Corporation), 2016)
"Rising income inequality has the potential to affect outcomes for children whose parents are at the lower end of the income scale by curtailing their opportunities. This report aims to understand the extent to which inequalities in opportunity and outcomes are related--and the mechanisms that drive that relationship--to help evaluate which policies have the most potential to level the playing field. This report reviews recent trends in inequality in outcomes (particularly, income inequality) and proxies for inequality of opportunity (measures of intergenerational transmission of income) and presents evidence on the extent to which they are correlated across countries and within countries across time. We discuss the evidence that shows that inequality in income and wealth has been increasing in the United States and most developed countries since the 1980s and that income inequality and inequality of opportunity are correlated across countries, but proxy measures for inequality of opportunity do not show the same consistently upward trend that was experienced by income inequality. The report then presents a framework to understand the mechanisms underlying the relationship between inequalities in income and opportunity. In light of this framework, we discuss the potential effects of policies on both income and inequality opportunity, and how these can be quantitatively assessed"--Publisher's description